Plasma 25-Hydroxyvitamin D Levels, Vitamin D-Related Genes and Risk of Type 2 Diabetes: Case-Control Study in a Costa Rican Population - Monge Rodríguez, Silvia Leticia (2022)
Aim: This research aimed to investigate the association between 25-hydroxyvitamin D plasma levels, gene polymorphisms, and the risk of type 2 diabetes in Costa Ricans. Methods: 578 adults were involved in a case-control study from an urban Costa Rican population. Blood samples were collected to measure circulating vitamin D levels, glucose, glycated hemoglobin, lipid profile, and for the genotyping of 14 vitamin-D related SNPs. The association of plasma levels of 25-hydroxyvitamin D, clinical and biochemical variables, gene polymorphisms and type 2 diabetes was tested. Results: There was an association of 25-hydroxyvitamin D levels with type 2 diabetes (OR: 0.97, CI 95%, 0.94 – 0.99) but a strong association was found between type 2 diabetes and classical risk factors as body mass index (OR: 1.13, CI 95%, 1.07 – 1.18) and arterial hypertension (OR: 3.31, CI 95%, 2.04 – 5.37). Plasma 25-hydroxyvitamin D were lower when age (β standardized: -0.23, CI 95%: -0.25 – -0.11), and body mass index (β standardized, CI 95%: -0.50 – -0.21) increase. GC gene polymorphisms (rs4588, rs7041, rs3755967, and rs22522679) were associated with plasma levels of vitamin D ( p values <0.036). None of the SNPs were associated with type 2 diabetes. Conclusion: Plasmatic levels of 25-hydroxyvitamin D are associated with SNPs located in the GC gen. As a risk factor for type 2 diabetes, it seems to have low influence compared to classical risk factors such as hypertension, obesity, and dyslipidemia, which showed a high prevalence in the sample.